2008
DOI: 10.1590/s1413-70542008000100033
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físicas do feijão durante a secagem: determinação e modelagem

Abstract: RESUMOAs propriedades físicas dos produtos agrícolas são influenciadas diretamente pela secagem. Assim, buscou-se com o presente trabalho avaliar o efeito do teor de água nas propriedades físicas dos grãos de feijão da cultivar Vermelho Coimbra, e ajustar diferentes modelos matemáticos aos valores experimentais. Analisaram-se duas metodologias para a determinação da massa específica aparente e da massa específica unitária. A massa específica aparente e a porosidade da massa foram determinadas utilizando-se uma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
24

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 11 publications
(8 reference statements)
3
10
0
24
Order By: Relevance
“…The porosity values of the safflower grain mass decreased along the drying ( Figure 2B), a common trend for many agricultural products (Isik & Izli, 2007;Zewdu & Solomon, 2007;Resende et al, 2008;Seifi & Alimardani, 2010b;Siqueira et al, 2012a). This trend can be explained, because agricultural products have, as a characteristic with the reduction of the moisture content, the reduction of their volume, causing the mass of the product to compact, reducing the intergranular spaces.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The porosity values of the safflower grain mass decreased along the drying ( Figure 2B), a common trend for many agricultural products (Isik & Izli, 2007;Zewdu & Solomon, 2007;Resende et al, 2008;Seifi & Alimardani, 2010b;Siqueira et al, 2012a). This trend can be explained, because agricultural products have, as a characteristic with the reduction of the moisture content, the reduction of their volume, causing the mass of the product to compact, reducing the intergranular spaces.…”
Section: Resultsmentioning
confidence: 83%
“…The values of bulk density decreased with the reduction in the moisture content of the safflower grains (Figure 2A), but agricultural products usually have the opposite trend for this property (Milani et al, 2007;Resende et al, 2008;Tavakoli et al, 2009;Seifi & Alimardani, 2010a;Jesus et al, 2013). However, Seifi et al (2010), working with safflower grains, variety Goldasht, found a similar trend to that found in the present study, as already observed for other crops, such as jatropha seeds (Siqueira et al, 2012a), melon seeds (Bande et al, 2012) and pistachio grains .…”
Section: Resultsmentioning
confidence: 99%
“…Resumo da análise de variância para as massas específicas aparente e unitária e porosidade das sementes de pinhão-manso submetidos a diferentes condições de secagem. (COUTO et al, 1999;ANDRADE, 2000;RIBEIRO et al, 2005;RAZAVI et al, 2007;RESENDE et al, 2008b;CHAVES, 2012b , para sementes de pinhão-manso com teor de água entre 4,75 e 19,57 (% b.u.). Logo é possível afirmar que além do teor de água a massa específica aparente é influenciada pelo processo de adsorção ou dessorção, que consiste em ganho e perda de água, respectivamente (CORRÊA et al, 2006).…”
Section: Resultsunclassified
“…Isso pode estar relacionado às características de rigidez apresentada pelo tegumento das sementes dessas espécies. Resultados semelhantes foram observados para sementes de feijão (RESENDE et al, 2008b) Nota-se ainda nas Figuras 3 e 4 que a variação das massas específicas aparente e unitária em função da redução do teor de água pode ser descrita por meio de modelos lineares, como observado por diversos pesquisadores (DEMIR et al, 2002;BARYEH;MANGOPE, 2002;ABALONE et al, 2004;RIBEIRO et al, 2005;NIMKAR, MANDWE;DUDHE, 2005;RESENDE et al, 2008b;PRADHAN et al, 2009). …”
Section: Resultsunclassified
“…At the post-harvest stage, drying is the most widely used process to assure beans quality and stability taking into account that reducing the moisture content of the material reduces biological activity as well as chemical and physical changes that occur during storage (RESENDE et al, 2008a). However, drying at temperatures and air moisture that generate large rates of water removal can substantially affect seed quality (ALMEIDA et al, 2009).…”
Section: Introductionmentioning
confidence: 99%